Stress-Strain State of a Cylindrical Shell of a Tunnel Using Construction Stage Analysis - Kosytsyn, Sergey B.; Akulich, Vladimir Y. (Communications - Scientific Letters of the University of Zilina, 2019)
The work is aimed at research of the stress-strain state of a cylindrical shell of a tunnel using the non-linear static analysis and construction stage analysis. Research is carried out on the example of determining the stress-strain state of the tubing (shells) of the main line tunnel, constructed using a tunnel powered complex (slurry shield). Based on obtained results, a comparative analysis of the computational models with the corresponding conclusions is presented.
Keywords: construction stages; soil massif; shell; slurry shield; finite elements